Development and application of a closed-loop medication administration system in University of Hongkong-Shenzhen Hospital - Shi Lan-Ping; Liu Chun-Hong; Cao Jian-Fen; Lu Yan; Xuan Fan-Xin; Jiang Yu-Ting; Zhou Jin-Yang (Sciendo, 2018)
This study aimed to develop and apply a closed-loop medication administration system in a hospital in order to reduce medication administration errors (MAEs).